Cincuentenario de la muerte del ilustre maestro de juventudes Dr. Arturo Orgaz - Luque, Martín ([Narvaja editor], 2005)
Participan: Martín Luque; Artura Orgaz; Mario Argüello; Francisco J. Gilardoni; Juan Luis Fernández; Efraín U. Bischoff; Raúl Faure; Dardo Ferreyra.